Plasma Atherogenic Index in Type 2 Diabetes Mellitus Patients (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction:Atherogenic index of plasma (AIP) is defined as log of TG to HDL-C ratio. People with high AIP have a higher risk for coronary heart disease (CHD) than those with low AIP. AIP is useful in predicting atherogenecity.Objectives:  To determination of AIP among the study subjects and find out the prevalence of AIP among type 2 diabetes mellitus (DM) patients.Materials and Methods: This cross sectional study was conducted at Armed Forces Institute of Pathology (AFIP) from November 2014 to October 2015. The study included 300 type 2 DM patients belonging to the age group 30-60 years. Fasting plasma glucose (FPG), HDL-C, TG were estimated. The AIP was calculated as log (TG/HDL-C) using the Czech online calculatorof atherogenic risk. Personal data and history of co-existing medical conditions were collected by data collection sheet. Data were analyzed by SPSS version 18.0.Results: Among 300 study subjects the AIP were found in the range of “increased risk” in 298(99.3%) and “low risk” in 02(0.7%). In this study mean FPG was 9.81±3.08 mmol/L and mean AIP was 0.73 ± 0.23A and significant positive correlation between FPG and AIP (r = 0.123, p < 0.05) was observed.Conclusion: The study revealed that AIP is significantly higher in type 2 DM patients. So, patients with type 2 DM should be followed up with AIP regularly.JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 204-205